2004
DOI: 10.1590/s0102-37722004000100008
|View full text |Cite
|
Sign up to set email alerts
|

A memória dos idosos em tarefas complexas

Abstract: 1 Este artigo está baseado na dissertação de mestrado do primeiro autor sob a orientação do segundo. Os autores agradecem aos participantes dos experimentos e aos revisores que contribuíram para o aprimoramento deste artigo. Aging and Memory in Complex TasksABSTRACT -Two experiments tested young and elderly participants in free recall, intra-list and extra-list cued recall. The first study investigated the effects of task complexity, age and stimulus presentation rate on free recall of words presented within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
1
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
1
1
7
Order By: Relevance
“…Previous Brazilian studies 26,27,28 indicated that older participants tend to have worse performance on cognitive tasks. For instance, Kochhann et al 29 studied 963 women aged between 20 and 92 years, in order to assess the independent effect and interactions between age, gender and education on the MMSE and noted that education and age influenced the MMSE scores.…”
Section: Discussionmentioning
confidence: 93%
“…Previous Brazilian studies 26,27,28 indicated that older participants tend to have worse performance on cognitive tasks. For instance, Kochhann et al 29 studied 963 women aged between 20 and 92 years, in order to assess the independent effect and interactions between age, gender and education on the MMSE and noted that education and age influenced the MMSE scores.…”
Section: Discussionmentioning
confidence: 93%
“…Entretanto, apenas em alguns casos o declínio cognitivo evolui para a demência 1,2 . O idoso que apresenta algum prejuízo mnemônico, mesmo que não patológico, em tese, pode queixar-se da memória com maior frequência.…”
Section: Introductionunclassified
“…Com base na literatura (Coney, 2002;Janczura, 1996;Van Erven & Janczura, 2004), considerou-se como associação semântica forte palavras geradas por, pelo menos, 25% da amostra e como associação semântica média palavras geradas por 10 a 24% da amostra. Por fim, palavras com associação semântica fraca foram aquelas geradas por menos de 10% da amostra.…”
Section: Resultsunclassified
“…Em relação à média de força de associação da lista como um todo, o valor é considerado como característico de forte associação entre os pares, conforme critérios da literatura (Coney, 2002;Janczura, 1996;Van Erven & Janczura, 2004). Janczura (1996) considerou 21% de ocorrência como forte associação semântica e Van Erven e Janczura (2004) consideraram associação forte uma média de 28% e associação fraca uma média de 2%.…”
Section: Discussionunclassified
See 1 more Smart Citation